An approach in solving Arabic grammatical errors among advanced Arabic language learners in Arabic for Academic Purposes Course at International Islamic University Malaysia = الوسائل المقترحة لحل المشكلة الأخطاء النحوية لدى المتقدمين من طلاب اللغة العربية لأعراض أكادمية في الجامعة الإسلامية بماليزيا - Masoud, Mahadi; Jalil, Marsufah (International Islamic University Malaysia, 2015)
The teaching and learning of Arabic language develops with the development of social life. The field of teaching Arabic also broadens with the increasing purposes of learning Arabic.